2012
DOI: 10.1007/s10681-011-0617-5
|View full text |Cite
|
Sign up to set email alerts
|

Diploid and tetraploid progenitors of wheat are valuable sources of resistance to the root lesion nematode Pratylenchus thornei

Abstract: The root lesion nematode Pratylenchus thornei is widely distributed in Australian wheat (Triticum aestivum) producing regions and can reduce yield by more than 50%, costing the industry AU$50 M/year. Genetic resistance is the most effective form of management but no commercial cultivars are resistant (R) and the best parental lines are only moderately R. The wild relatives of wheat have evolved in P. thornei-infested soil for millennia and may have superior levels of resistance that can be transferred to comme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
13
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(14 citation statements)
references
References 58 publications
1
13
0
Order By: Relevance
“…The broad‐sense heritability estimates reported in this study indicate resistance to P. neglectus and P. thornei are moderately heritable under the evaluation conditions used in this study. Previous estimates of broad‐sense heritability have been as low as 25% for P. neglectus in barley ( Hordeum vulgare L.; Sharma et al, 2011) and as high as 94% for P. thornei in wheat (Sheedy et al, 2012). Narrow‐sense heritability estimates have been reported between 63 and 87% for P. neglectus and between 89 and 93% for P. thornei (Thompson et al, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…The broad‐sense heritability estimates reported in this study indicate resistance to P. neglectus and P. thornei are moderately heritable under the evaluation conditions used in this study. Previous estimates of broad‐sense heritability have been as low as 25% for P. neglectus in barley ( Hordeum vulgare L.; Sharma et al, 2011) and as high as 94% for P. thornei in wheat (Sheedy et al, 2012). Narrow‐sense heritability estimates have been reported between 63 and 87% for P. neglectus and between 89 and 93% for P. thornei (Thompson et al, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…Their results indicated no complete resistance and no relationship between H. filipjevi and P. thornei resistance. These most likely have quantitative resistance genes against both CCNs and RLNs (Toktay et al, 2006;Sheedy et al, 2012). However, it is clear that while the Cre genes provide resistance to H. avenae, they do not confirm resistance to the H. filipjevi Turkish population.…”
Section: Discussionmentioning
confidence: 96%
“…Tritcum urartu is a potentially important source of genetic variation for a wide variety of agronomically important traits ( Austin et al, 1982 ; Qiu et al, 2005 ; Martín et al, 2008 ; Rouse and Jin, 2011 ; Sheedy et al, 2012 ). Using the ph1 mutant approach, wheat- T. urartu recombinant lines have been generated in this study (Figure 1 ) suggesting that recombination can occur between hexaploid wheat and T. urartu chromosomes.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, interspecific crossing between T. urartu and bread wheat would potentially enable transfer of desirable traits from the chromosomes of the wild diploid wheat into cultivated hexaploid wheat through direct hybridization. Previous research has shown that T. urartu carries many agronomically important traits, such as high net photosynthetic rate ( Austin et al, 1982 , 1986 ; Morgan and Austin, 1986 ) and disease resistance ( Rouse and Jin, 2011 ; Sheedy et al, 2012 ), which can be exploited for improving wheat’s narrow gene pool ( Qiu et al, 2005 ; Martín et al, 2008 ).…”
Section: Introductionmentioning
confidence: 99%